E-portfolio in postgraduate education system of teachers of higher medical (pharmaceutical) educational institutions: psychological and pedagogical aspect - M. M. Filonenko; Kh. V. Podkovko (Academy of Cognitive and Natural Sciences, 2017)
This publication aims to prove the rationale for use of the e-portfolio in postgraduate education system of teachers of higher medical (pharmaceutical) educational institutions. Object of research: process of professional training of the teacher of higher medical (pharmaceutical) educational institution for scientific and educational activities in postgraduate education system. Subject of research: use of the e-portfolio technology in postgraduate education system by teachers of higher medical (pharmaceutical) educational institutions. The following research methods were applied while preparing this publication: analysis of regulatory documents, psychological, educational, instructional materials, theses, conference proceedings and periodical professional publications; generalization and systematization of positions of leading scientists; comparison and collation of different views on the issue; empirical research through questionnaires. As a result of the research, we have concluded that the management of higher medical (pharmaceutical) educational institutions are not fully aware of the potential of the e-portfolio in formation of professional competence, particularly psychological and educational one. In order to enhance understanding of the contents and purpose of the e-portfolio technology, experience of Pedagogy and Psychology of Postgraduate Education Department at Bogomolets National Medical University was illustrated. Application of the e-portfolio technology, as one of the means to form psycho-pedagogical competence of the teacher of higher medical (pharmaceutical) educational institution, will improve the quality of their professional competence, given the current demands of society and changes in the European integration with regard to higher education system.